Hubungan Trait Kepribadian Ekstraversi dengan Perilaku Agresif pada Remaja di SMK YARSI Mataram - Romadonika, Fitri; Hidayati , Baiq Nurul; Mutia, Vista Fatimah (JURNAL KESEHATAN TROPIS INDONESIA, 2026)
Aggressive behavior among adolescents is influenced by various factors, one of which is the extraversion personality trait. Individuals with higher levels of extraversion tend to exhibit characteristics such as impulsivity and risk-taking, which may increase the likelihood of aggressive behavior. Objective: This study aimed to analyze the relationship between the extraversion personality trait and aggressive behavior among adolescents at SMK YARSI Mataram. This study employed an analytical correlational design with a cross-sectional approach. A total of 80 respondents were selected using a simple random sampling technique. Data were analyzed using Spearman's rank correlation test. Most respondents had a moderate level of the extraversion personality trait (62.5%) and a moderate level of aggressive behavior (51.3%). The results of Spearman's correlation test showed a significant relationship between the extraversion personality trait and aggressive behavior among adolescents (p < 0.001). It can be concluded that the extraversion personality trait is significantly associated with aggressive behavior among adolescents at SMK YARSI Mataram. These findings may serve as a basis for schools to develop promotive and preventive programs aimed at reducing aggressive behavior among adolescents.